Penerapan Business Model Canvas (BMC) pada Bisnis Jasa Fotografi Produk Rabbithall Studio - Hasna Nabiilah Widiani; Muhammad Fillah Alfatih; Thoriq Muhammad Pasya; Wien Kuntari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The growth of digital technology has significantly transformed the marketing strategies employed by micro, small, and medium enterprises. Within an increasingly competitive digital marketing ecosystem, high-quality visual branding serves as a crucial component in capturing consumer attention and enhancing brand awareness. However, the enterprises frequently encounter constraints related to budget, technology, and expertise in producing effective visual content. In response to these challenges, Rabbithall Studio offers a solution by providing affordable, high-quality content, particularly for enterprises that operating in the foods and beverages sector. This research aims to design a Business Model Canvas (BMC) for Rabbithall Studio to effectively support the digital marketing strategy of MSMEs. A descriptive qualitative approach is used to analyze key elements in the BMC, such as customer segments, value propositions, distribution channels, and cost structure. The research findings reveal that Rabbithall Studio has a strategic business model, focusing on providing aesthetic and Instagrammable product photography services, along with copywriting support. This study offers a strategic guide for MSMEs to adopt visual and content-based marketing to enhance their competitiveness in the digital market.